(3GdcJGH GdKGfjs - (3QhHQJ(B, (3cdjeGfs; (3SQhQ Ydj GHQGgje SQhQ(B, s ((3GdQjGV (B/ (3OGQ GdeQjN(B:s, 2010)
2 ) (3fePLI YOe GdJCcO (B: (3feGPL GdGMJeGd GdfXQjI , GSJNOGe GdHjGfGJ h eMGcGI ehfJ cGQdh , bjeI GdeYdheGJ (B: (3GdGSJKeGQ aj Shb GdChQGb GdeGdjI h GdGYUGQGJ GdfHJjI (B3) (3fePLI GdJaVjdGJ (B: (3ehGba GdeNGWQI eMGQHI gGQjeGf ef CLd NW ScI MOjO TeGd GdHGSajc , HOjgjGJ GdefaYI h XGgQjGJ GdJfGbV h GdJVejfGJ , GdCgOGa GdeJYGQVI (B: (3GdCgOGa GdCSGSjI h OGdI GdefaYI GdLeYjI , feGPL GdefaYI eJYYOI GdNhGU eY GdJOGNdGJ (B.s
(3edGMb U(B.1017s
Keywords: (3EJNGP GdbQGQs; (3GdGLQGAGJ GdGOGQjIs; (3GdbQGQGJ GdGOGQjIs